Leslie f*cking Jones : a memoir - Jones, Leslie, 1967- (Grand Central Publishing, 2023)
A candid memoir filled with vivid anecdotes: Growing up in the South, navigating stand-up comedy's challenging early days, brushes with celebrities like Chris Rock and Whoopi Goldberg, and insights on Ghostbusters, Supermarket Sweep, The Daily Show. Revealing struggles as a tall Black woman in comedy.